The Comparison of Family Functioning Dimensions and Quality of Life and their Relationships among Addicted and Non-Addicted Persons - Mohammad Ghamari (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The aim of this study was the comparison of family functioning and quality of life and their relationships among addicted and non-addicted persons. Method: The research method of study was ex-post factor. The sample of study was 107 addicts and 107 non-addicts. Sampling of addicts was clustering random sampling. Non-addicts were matched in terms of demographical characteristics and were selected of normal population. Measuring instruments were family assessment device and quality of life scale (SF-36). Statistical methods were Pearson correlation coefficient, stepwise regression analysis and independent samples t test. Results: The results showed that the dysfunction in family function among addicts was more than non-addicts counterparts. Addicts have had lower quality of life than non-addicts. Also, there was significant relationship between dimensions of family functioning and quality of life among addicts and non-addicts. The results of regression analysis showed that almost 17 percent of quality of life variance among addicts could be explained by dimensions of family functioning namely: roles and communication. Among non-addicts about 17 percent of quality of life variance could be explained by behavior control dimension of family functioning. Conclusion: The study may have useful practical implications for executors of addiction prevention also addiction therapists.